2020
DOI: 10.1093/nar/gkaa417
|View full text |Cite
|
Sign up to set email alerts
|

Design, optimization and analysis of large DNA and RNA nanostructures through interactive visualization, editing and molecular simulation

Abstract: Abstract This work seeks to remedy two deficiencies in the current nucleic acid nanotechnology software environment: the lack of both a fast and user-friendly visualization tool and a standard for structural analyses of simulated systems. We introduce here oxView, a web browser-based visualizer that can load structures with over 1 million nucleotides, create videos from simulation trajectories, and allow users to perform basic edits to DNA and RNA designs. We add… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 58 publications
1
116
0
Order By: Relevance
“…Because of the different structural design methods for W and L, they are expected to possess differences in local rigidity and propensity for thermal fluctuation. The mean structures, which were computed from oxDNA molecular dynamics simulation 40,41 in 500 mM Na + (simulation parameter), showed that the L-type structure tended to stay flatter than the W types( Fig.1e). Root mean square fluctuation (RMSF) values of the Ws are estimated to be around 5-time higher than those of the Ls (Fig.1e), further validating its higher local structural flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the different structural design methods for W and L, they are expected to possess differences in local rigidity and propensity for thermal fluctuation. The mean structures, which were computed from oxDNA molecular dynamics simulation 40,41 in 500 mM Na + (simulation parameter), showed that the L-type structure tended to stay flatter than the W types( Fig.1e). Root mean square fluctuation (RMSF) values of the Ws are estimated to be around 5-time higher than those of the Ls (Fig.1e), further validating its higher local structural flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…This model can also be used to predict the involved forces when unraveling a DNA origami by force-induced melting, and it has been experimentally verified via Atomic Force Microscope (AFM), making it an interesting example for the flexibility of this software [ 98 ]. A recently-developed web browser-based visualization tool, oxView, provides a fast and user-friendly interface to the underlying code, and it includes additional modules for characterizing aspects, such as structural [ 99 ], and a tool, TacoxDNA, is also available for converting common CAD output files (e.g., from Cadnano or Tiamat) into representations that are suitable for simulation via OxDNA [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…(v) [ 28 ], Copyright The American Association for the Advancement of Science, 2016. (bottom left to right): (i) Holiday junction was created using oxView [ 99 ]. (v) [ 28 ], Copyright The American Association for the Advancement of Science, 2016.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The oxDNA topology and configuration files are then imported to oxDNA to evaluate structural validation. The results from oxDNA are analyzed using the RMSF scripts and visualized in oxView, which are both developed by Poppleton et al [39]. The last frame of the oxDNA simulation is then converted to PDB using TacoxDNA.…”
Section: Applicationsmentioning
confidence: 99%